2021
DOI: 10.3389/fneur.2021.697349
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gray Matter Volume, Functional Connectivity, and Degree Centrality in Early-Onset Type 2 Diabetes Mellitus

Abstract: Background: Structural and functional brain alterations that underlie cognitive decline have been observed in elderly adults with type 2 diabetes mellitus (T2DM); however, whether these alterations can be observed in patients with early-onset T2DM remains unclear. Therefore, we aimed to describe the abnormalities in brain volume and functional patterns in patients with early-onset T2DM in the present study.Methods: We enrolled 20 patients with early-onset T2DM and 20 healthy controls (HCs). Changes in brain vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…The full-text of remained 120 results were read, and 104 results of which were removed. In the end, total 15 studies (16 datasets) meeting the inclusion criteria were included in this study, which consisted of 11 GM datasets including 7 GMV [15,[35][36][37][38][39][40], 2 gray matter density (GMD) [40][41][42], and 2 cerebral cortical thickness [14,16], as well, as 5 WM datasets including 5 FA abnormality [16,[43][44][45][46]. The detailed search flow diagram was showed in Fig.…”
Section: Systemic Search Information and Characteristics Of Included ...mentioning
confidence: 99%
“…The full-text of remained 120 results were read, and 104 results of which were removed. In the end, total 15 studies (16 datasets) meeting the inclusion criteria were included in this study, which consisted of 11 GM datasets including 7 GMV [15,[35][36][37][38][39][40], 2 gray matter density (GMD) [40][41][42], and 2 cerebral cortical thickness [14,16], as well, as 5 WM datasets including 5 FA abnormality [16,[43][44][45][46]. The detailed search flow diagram was showed in Fig.…”
Section: Systemic Search Information and Characteristics Of Included ...mentioning
confidence: 99%
“…(Detailed general demographic, clinical, and radiographic features are shown in Tables 1-4) On the one hand, we observed an unbalanced sex distribution between T2DM and HCs in the first group ( x 2 = 13.423, P < 0.001). Significant differences were observed between T2DM and HCs regarding age Among them, there was a gender-specific study (123), two education-level studies (121,123), two MMSEs (16,17), and six MOCA studies (11,15,21,(120)(121)(122)…”
Section: Eligible Studies and Sample Characteristicsmentioning
confidence: 99%
“…Multiple functional and cerebral perfusion indicators such as ALFF, ReHo, ICA, DC, and CBF were used to explore the brain alteration in patients with T2DM, and previous studies showed many functional indicators in the anterior cingulate gyrus, posterior cingulate gyrus, and frontal lobe (10)(11)(12)(13)(14). Although the changes in some brain regions were consistent when using different MRI indicators, the studies also found that a large number of brain regions were inconsistent (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). This may be due to limited sample size, differences in general clinical patient data, and different methods of measuring the brain activity.…”
Section: Introductionmentioning
confidence: 96%
“…T2D is associated with neuronal degeneration (Madhusudhanan et al, 2020;Yu et al, 2021), and a variety of neurodegenerative diseases are accompanied by gray matter (GM) abnormalities (Last et al, 2017). Previous studies have documented alterations in GM in T2D patients (Garcia-Casares et al, 2014;Liu et al, 2017;Redel et al, 2018;Roy et al, 2020;Feng et al, 2021). Roy et al declared that T2D patients had gray matter volume (GMV) reductions in the prefrontal, hippocampus, amygdala, insular, cingulate, cerebellum, caudate, basal-forebrain, and thalamus compared with healthy controls (HCs) (Roy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Roy et al declared that T2D patients had gray matter volume (GMV) reductions in the prefrontal, hippocampus, amygdala, insular, cingulate, cerebellum, caudate, basal-forebrain, and thalamus compared with healthy controls (HCs) (Roy et al, 2020). Early-onset T2D patients had decreased GMV in the left orbital superior, middle, and inferior frontal gyri, as well as the right superior frontal gyrus, compared to HCs (Feng et al, 2021). Liu et al considered cortical-striatal-limbic networks to be the main sites of GMV loss in T2D patients (Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%